Forensic casework in contemporary perspective - Ubelaker, Douglas H. (Anthropological Review, 2012)
Recent developments have changed forensic casework in largely positive ways. New technology, expanded databases, enhanced statistical treatment and improved laboratory procedures enable better interpretation of evidentiary analysis and more thoughtful summaries presented in reports and testimony. Increased scrutiny has focused attention on the need for advancement in forensic science through research and structural adjustments.